2013
DOI: 10.1021/bi400546j
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Enzyme–Substrate Specificity with QM/MM Methods: A Case Study of the Stereospecificity of d-Glucarate Dehydratase

Abstract: The stereo-specificity of D-glucarate dehydratase (GlucD) is explored by QM/MM calculations. Both the substrate binding and the chemical steps of GlucD contribute to substrate specificity. Although the identification of transition states remains computationally intensive, we suggest that QM/MM computations on ground states or intermediates can capture aspects of specificity that cannot be obtained using docking or molecular mechanics methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Until now, several strategies have been successfully used for prediction of enzyme function such as structure-based docking of high-energy intermediates, combining quantum mechanics and molecular mechanics (QM/MM) methods to determine substrate specificity and comparison of putative active site to the active sites of structurally and functionally characterized enzymes. The molecular mechanics based scoring functions cannot accurately describe the electronic structures of the transition state . Therefore, a combination of quantum mechanics and molecular mechanics methods (QM/MM) is useful to give more accurate analysis of not only the mechanism but also the substrate specificities of enzymes . However, this method is computationally expensive.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now, several strategies have been successfully used for prediction of enzyme function such as structure-based docking of high-energy intermediates, combining quantum mechanics and molecular mechanics (QM/MM) methods to determine substrate specificity and comparison of putative active site to the active sites of structurally and functionally characterized enzymes. The molecular mechanics based scoring functions cannot accurately describe the electronic structures of the transition state . Therefore, a combination of quantum mechanics and molecular mechanics methods (QM/MM) is useful to give more accurate analysis of not only the mechanism but also the substrate specificities of enzymes . However, this method is computationally expensive.…”
Section: Introductionmentioning
confidence: 99%
“…This docking protocol was successfully applied to design cpADH5 variants by selecting the catalytic docking pose of substrates from the cluster of docking poses. 20 Until now, several strategies have been successfully used for prediction of enzyme function such as structure-based docking of high-energy intermediates, 21 combining quantum mechanics and molecular mechanics (QM/MM) methods to determine substrate specificity 22 and comparison of putative active site to the active sites of structurally and functionally characterized enzymes. 23−26 The molecular mechanics based scoring functions cannot accurately describe the electronic structures of the transition state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quasi single-model methods overcome this limitation by creating a model ensemble 'on the fly' so that, from a user perspective, the assessment of a single model becomes possible (Roche et al, 2014). modeling community, such as modeling oligomeric states and complexes (Biasini et al, 2014;Shapovalov et al, 2014), modeling the binding sites of functionally relevant ligands and cofactors (Gallo Cassarino et al, 2014), refining models closer to the native structure (Nugent et al, 2014) or predicting the substrate specificity of enzymes (Tian et al, 2013).…”
Section: Assessment Of Homology Modeling Methods: Casp and Cameomentioning
confidence: 99%
“…In principle, combining quantum mechanics and molecular mechanics methods (QM/MM) can provide more accurate analysis of the mechanisms and specificities of enzymes. A proof-of-concept study has shown that such an approach may become practical for studying certain challenging aspects of enzyme specificity, compared to the more common use of quantum mechanical methods to investigate reaction mechanisms [38]. In the future, this type of approach may be particularly important when studying enzymes with intermediates that are radicals (e.g.…”
Section: Using Structure To Infer Small Molecule Bindingmentioning
confidence: 99%